On the structure of two-periodic cube tilings of the 4-dimensional Euclidean space - Sikiric, Mathieu Dutour; Tysakowska, Magdalena (Utilitas Mathematica, 2019)
Two-periodic unit cube tilings of the 4-dimensional Euclidean space are classified. This paper contains the algorithm one used to do the classification and obtained results. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.